Clusterin and Related Scoring Index as Potential Early Predictors of Response to Sorafenib in Hepatocellular Carcinoma. Issue 5 (27th November 2021) - Narahara, Satoshi; Watanabe, Takehisa; Nagaoka, Katsuya; Fujimoto, Nahoko; Furuta, Yoki; Tanaka, Kentaro; Tokunaga, Takayuki; Kawasaki, Takeshi; Yoshimaru, Yoko; Setoyama, Hiroko; Oniki, Kentaro; Saruwatari, Junji; et al.
Abstract : Advanced hepatocellular carcinoma (HCC) remains a highly lethal malignancy, although several systemic therapeutic options are available, including sorafenib (SFN), which has been one of the standard treatment agents for almost a decade. As early prediction of response to SFN remains challenging, biomarkers that enable early prediction using a clinically feasible method are needed. Here, we report that the serum secretory form of clusterin (sCLU) protein and its related predictive index are potential beneficial biomarkers for early prediction of SFN response. Using high‐throughput screening and subsequent multivariate analysis in the derivation cohort, we found that changes in the concentrations of CLU, vascular cell adhesion molecule‐1 (VCAM1), and α‐fetoprotein were significantly associated with response to SFN. Furthermore, we confirmed that an increase in CLU serum level 1 month after treatment initiation was significantly associated with shorter progression‐free survival. In addition, "NR‐index, " which comprises these proteins, was evaluated as a tool for accurately predicting the efficacy of SFN and confirmed in the validation cohort. We also established SFN‐resistant HepG2 cells (HepG2‐SR) and found that sCLU significantly increased in HepG2‐SR cells compared with normal HepG2 cells, and confirmed that HepG2‐SR cells treated with SFN were resistant to apoptosis. The mechanism underlying activation of sCLU expression in acquired SFN resistance involves aberrant signaling and expression of Akt, mammalian target of rapamycin (mTOR), and a nutrient‐related transcription factor, sterol regulatory element binding protein 1c (SREBP‐1c). Furthermore, the PI3K and mTOR inhibitor BEZ235 markedly decreased sCLU expression in HepG2‐SR cells. Conclusion: These results suggest that measurement of sCLU serum levels and the sCLU‐related NR‐index are promising clinical tools for the early prediction of SFN response in HCC. Additionally, sCLU‐overexpressing HCC might be susceptible to mTOR inhibition. Abstract : Sorafenib is one of the molecular‐targeted agents for advanced hepatocellular carcinoma, therefore it is necessary to predict treatment response to sorafenib earlier and inform the switch to other therapies as quickly as possible after sorafenib‐treatment failure. In this study, we aimed to identify serum biomarkers and establish a formula for predicting sorafenib treatment response at an early stage after treatment initiation using paired serum samples from advanced hepatocellular carcinoma patients, and found that a novel serum biomarker, clusterin related predictive index scoring "NR‐index" could be a promising clinical formula for early prediction of the efficacy of sorafenib. Finally, we clarified the molecular mechanism underlying sorafenib resistance using sorafenib‐resistant HepG2 cells.